Changes in COVID-19 Perception and in TMD Prevalence after 1 Year of Pandemic in Italy - Scelza, Giuseppe; Amato, Alessandra; Rongo, Roberto; Nucci, Ludovica; D'Ambrosio, Francesco; Martina, Stefano (European Journal of Dentistry, 2022)
Objectives The study aims to report the perception of dental practices and assess the individual's psychological stress level and related temporomandibular disorders (TMD) symptoms by evaluating the changes that occurred during the year following the first lockdown (May 2020).Materials and Methods An online questionnaire was submitted to the Italian population between 20 March and 20 April 2021. It was sent via online platforms and included 14 questions.Statistical analysis The data were analyzed using a chi-squared test and a comparison of the current data with the May 2020 survey data was performed using independent samples t-tests. The level of significance was set at p < 0.05.Results Forty-three percent of subjects (872) considered the dental practice to be a place with a high risk of infection. Temporomandibular pain and joint sounds were reported by 35.7% (724) of the population; of these more frequently were women (71.8%, 520/724, p < 0.001). About 31% of the participants had moderate/severe psychological distress and, among them, it was found that 46.4% (294/634) reported TMD pain (p < 0.001) and 34.9% (221/634) complained of temporomandibular joint sounds (p < 0.001).Conclusions Most participants did not consider dental practices as a place with a higher risk of coronavirus disease 2019 transmission and, in contrast to the data from a previous study, people were less afraid to go to dental practices. After the first year of the pandemic, the level of stress and depression increased and the prevalence of TMD pain and joint sounds increased, in association with gender, age, and level of distress.
Keywords: COVID-19 pandemic; psychological stress; dental practice; survey; temporomandibular disorders; TMD pain